Spectrophotometry UV-Vis Technique Combined with Chemometrics for Determination Phenylbutazone and Acetaminophen In Herbal Medicines - Rollando Rollando (Journal of Global Pharma Technology, 2019)
Objective: Indonesia is known with its natural resources, one of them is abundant herbs. The herbs are basic ingredients of herbal medicine which is called jamu. Jamu started to develop since hundred years ago and passed through generation which is trusted to cure many diseases without giving any side effect. Lately, there are many cases of combining jamu with some chemical substances. The most common chemical substances used in jamu are acetaminophen and phenylbutazone. Methods: This research develops method to detect acetaminophen and phenylbutazone by using spektrofotometric UV-Vis which is combined with chemometrics. The most common chemometrics multivariate calibration used is Partial Least Square (PLS) and Principal Component Analysis (PCA). From this method, the data analysis used is R Studio software. This research generates a regression equation. Results: Based on this research, the regression equation indicates that the result is significance which can be seen from the value of P < 0.05. Besides that, the value of correlation coefficient of acetaminophen as 0.9889, and phenylbutazone as 0,9728. Conclusion:  This method can be considered as qualified and meet the requirement.